Analisis Employer Branding dengan Pendekatan Perilaku Kelompok (Studi Kasus Pada Forum Osis Jawa Barat Gen 8) - Sadiyah, Mima Halimatus (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2025)
The aim of this study is to determine the application of the employer branding model, identify the groups, determine the stage of group development, and determine the application of group property in the West Java OSIS Forum. This study is a descriptive study with a qualitative approach that focuses on existing phenomena that are then understood and analyzed in detail. This study is a descriptive study with a qualitative approach that focuses on existing phenomena that are then understood and analyzed in depth. This study describes an event that occurred in the West Java OSIS Forum environment with the research subjects being representatives of the group members.The sampling technique used is a snowball. The data source used in this study is primary data obtained through interviews and questionnaires conducted online. According to this study, the West Java OSIS Forum is considered a formal group that is currently in the performing stage, specifically in its eighth generation, which is currently in the adjourning stage.The West Java OSIS Forum has implemented a comprehensive employer branding model which has an impact on the increasing number of registrants each year and the quality of human resources, then similar student organizations can use the application of good group property as a reference when managing their groups.